Hollywood in Berlin : American cinema and Weimar Germany - Saunders, Thomas J. (University of California Press, 1994)
Charlie Chaplin, Hollywood's most famous film star, went almost unnoticed when he visited Berlin in 1921. Three years later, Jackie Coogan was mobbed by Berlin fans. Within two years after that, audiences were protesting with howls and angry whistling against the American motion pictures that dominated Berlin's leading theaters. Yet before the decade was over they were lining up to hear Al Jolson sing in their first experience of sound film. These roller-coaster reactions are engagingly documented by Thomas Saunders as he explores an outstanding example of one of this century's most important cultural developments: global Americanization through the motion picture. The setting is Berlin, the cultural heart of Central Europe and home of the only film industry after World War I to rival Hollywood's. The invasion by American films, which began in 1921 with overlapping waves of sensationalist serials, slapstick shorts, society pictures, and historical epics, initiated a decade of cultural collision and accommodation. It fueled an impassioned debate about the properties of cinema and the spectre of wholesale Americanization, while facilitating unprecedented levels of cultural and economic exchange.
Based on the author's thesis (doctoral).
Keywords: Motion pictures -- Germany -- History.; Motion pictures, American -- Germany -- Influence.; Motion pictures, German -- United States -- Influence.; National characteristics, American, in motion pictures.; National characteristics, German, in motion pictures.; Cinéma -- Allemagne -- Histoire.; Cinéma américain -- Allemagne -- Influence.; Cinéma allemand -- États-Unis -- Influence.; Américains au cinéma.; Allemands au cinéma.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film -- General.; Motion pictures; Motion pictures, American -- Influence; Motion pictures, German -- Influence; National characteristics, American, in motion pictures; National characteristics, German, in motion pictures; Germany; United States; History